Lectotypification of the name Carex curvata Knaf (Cyperaceae) with some taxonomic remarks - Řepka, Radomír; Więcław, Helena; Koopman, Jacob (Phytotaxa, 2023)
A lectotype is designated for the name Carex curvata Knaf on a herbarium specimen found in the PR (National Museum, Prague). The specimen we selected seems to correspond to the author’s original concept of the name as supported by the herbarium label written by the author of the name and including the same locality as mentioned in the protologue. The typification is supplemented with taxonomic notes on the determination of similar and related species.